A research on dust suppression mechanism and application technology in mining and loading process of burnt rock open pit coal mines. (2nd December 2021) - Zhao, Xiaoliang; Zhao, Xueying; Han, Fangwei; Song, Ziling; Wang, Dong; Fan, Junfu; Jia, Zhengzhao; Jiang, Guiguo
ABSTRACT: In order to solve the serious dust pollution problem in mining and loading process of burnt rock open-pit coal mines, a dust suppression technology was proposed to investigate the compound dust suppressant with four functions of wetting, coagulation, moisture absorption, and moisture retention, and improve the hydrophilicity and dust suppression efficiency of burnt rock. Through single-factor experiments, four functional reagents were selected. Determined the best mass concentration ratio by orthogonal test, and the optimum dilution ratio was determined through the contact angle verification test. Fourier infrared spectroscopy (FTIR) analysis of the functional group of the compound dust suppressant showed that the hydrophilic functional group was increased. The scanning electron microscopy (SEM) revealed that the dust surface formed a dense film after spraying the dust suppressant, and the effect of fine dust coagulation was obvious. The results of the wind tunnel simulation test revealed that the inhibitory efficiency of the compound dust suppressant on total dust and respirable dust could reach up to 81.90% and 87.06%, respectively, under a wind speed of 4.00 m/s. The field test data for mining and loading spray dust suppression in open-pit coal mines revealed that the dust suppression efficiency of whole dust and respirable dust was greater than 85.70%, which indicates that the compound dust suppressant can effectively suppress the dust of burnt rock, and effectively improve the working environment quality of mining and loading in open-pit coal mines. Implications : Open-pit coal mines located in arid areas will produce a large amount of dust during the mining and loading process, which will cause serious air pollution. In particular, the burnt rock is highly hydrophobic, and it is difficult to achieve effective removal by water spraying. The open-pit coal mine face advances faster and has strong mobility, There are few researches on dust reduction in this link. Therefore, in this study, in order to improve the dust suppression efficiency in the mining and loading process, a compound dust suppressant to improve the hydrophilicity of the burnt rock was developed through single-factor experiments and orthogonal experiments. Microscopic analysis using FTIR and SEM confirmed the wetting and coagulation effect of the dust suppressant. Then designed a spray dust suppression program for the mining and loading process and achieved good results.